The Effect of a Program based on Gardner’s Five Minds Theory on the Development of Undergraduate Mathematics Graduate Students’ Creative Thinking at the Faculty of Education - Sana’a University - Al-Maqtari, Eman Ahmed; Saeed, Radman Mohamad (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to identify the effect of a program based on Gardner’s Five Minds Theory on developing mathematics undergraduate students’ creative thinking at the College of Education, Sana’a University. The study adopted the experimental approach with a semi-experimental design based on one group. On Academic year 2021-2022. The sample of the study was consisting of 30 students. To achieve the aim of the study, the researchers built a creative thinking test, has acceptable validity and reliability. The researchers used the spss v.25 statistical package for analyzing the data statistically. The results of the study revealed that: There is significant statistical difference on the mean scores of the students in the pre and post application of the creative thinking test and in all its skills in favor of the post application. Also, the results showed there is high effect size for the program on the developing of Creative Thinking.